Identification and characterization of Septoria steviae as the causal agent of Septoria leaf spot disease of stevia in North Carolina. (4th May 2019) - Koehler, Alyssa M.; Larkin, Maximo T.; Rogers, Layne W.; Carbone, Ignazio; Cubeta, Marc A.; Shew, H. David
ABSTRACT: Stevia ( Stevia rebaudiana ) is an emerging perennial crop in the southeastern United States. A Septoria leaf spot disease of stevia was first identified on field plantings in Japan in 1978. The pathogen was named Septoria steviae based on a morphological characterization. In 2015, a species of Septoria with morphological characters of S. steviae was isolated from field and greenhouse-grown stevia plants with leaf spot symptoms in North Carolina. In this study, 12 isolates obtained from diseased stevia plants in 2015 and 2016 were characterized and compared with reference strains of S. steviae . Comparisons were based on conidial and pycnidial morphology and multilocus sequence analysis of actin ( ACT ), β-tubulin ( BT ), calmodulin ( CAL ), nuc rDNA internal transcribed spacers (ITS1-5.8S-ITS2 = ITS), nuc rDNA 28S subunit (28S), RNA polymerase II second largest subunit ( RPB2 ), and translation elongation factor-1α ( TEF1 ). Measurements of conidia and pycnidia from symptomatic field leaves and 12 pure cultures grown on nutrient medium were consistent with those previously reported for ex-type strains of S. steviae . North Carolina strains formed a well-supported monophyletic group with ex-type strains of S. steviae . This study represents the first genetic characterization of S. steviae in the United States and provides an experimental framework to elucidate the genetic diversity and disease ecology of field populations of S. steviae .